The Influence of Financial Technology on the Performance of MSMEs in the Regency Blitar : Effect Financial Literacy Mediation - Murdiono, Achmad; Zen, Fadia; Istanti, Lulu Nurul (CV. Proaksara Global Transeduka, 2024)
The Pancasila democratic economic system places MSMEs as one of the ideal locomotives for driving the national economy. Financial technology (Fintech) presents a paradigm shift in the financial and business sectors, one of which is the development of Fintech in the MSME scale industry. The focus object in this research is Blitar district MSMEs administrators who use fintech under the coordination of the Blitar District MSMEs and MSMEs Service. From variable testing, we can find out the impact of financial technology on the performance of MSMEs with financial literacy as a mediating variable. This research uses a quantitative approach which is descriptive, meaning that data analysis is quantitative, data collection uses research instruments which are also used to examine populations and samples to test the hypotheses that have been applied. The research results show that Fintech does not affect the performance of MSMEs and financial literacy is able to moderate the influence of Fintech on the performance of MSMEs. Variables such as sales turnover, profitability and asset growth do not show significant differences between MSMEs that use Fintech and those that do not use Fintech. These findings indicate that the benefits of Fintech have not been fully felt by MSMEs.